Observational Pain Assessment Instruments for Use With Nonverbal Patients at the End-of-life: A Systematic Review. Issue 4 (October 2019) - Tapp, Diane; Chenacher, Sara; Gérard, Ngangue Patrice Alain; Bérubé-Mercier, Philippe; Gelinas, Celine; Douville, Frédéric; Desbiens, Jean-François
Purpose: To review studies pertaining to the reliability and validity of observational pain assessment tools for use with nonverbal patients at the end-of-life, a field of research not documented by previous systematic reviews. Methods: Databases (PubMed, Embase, Epistemonikos, the Cochrane Library, and CINAHL) were systematically searched for studies from study inception to February 21, 2016 (update in May 9, 2018). Two independent reviewers screened study titles, abstracts, and full texts according to inclusion and exclusion criteria. Disagreements were resolved through consensus. Reviewers also extracted the psychometrics properties of studies of observational pain assessment instruments dedicated to a noncommunicative population in palliative care or at the end-of-life. A comprehensive quality assessment was conducted using the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) to derive poor, fair, good or excellent ratings for the psychometric tests reported in each study. Results: Four studies linked to 4 different tools met the inclusion criteria. Study populations included dementia, palliative care and severe illness in the context of intensive care. All the studies included in this review obtained poor COSMIN ratings overall. Conclusions: At this point, it is impossible to recommend any of the tools evaluated given the low number and quality of the studies. Other analyses and studies need to be conducted to develop, adapt, or further validate observational pain instruments for the end-of-life population, regardless of the disease.